Luís Natal ou Câmara Cascudo: o autor da cidade e o espaço como autoria - Sales Neto, Francisco Firmino (2009)
The objective of this work is to problematize a strong identification of Luís da Câmara Cascudo (1898-1986), a norte-riograndense author, to the city of Natal, analyzing the constitution of a spaciality that takes this author as this city s intellectual exponent and cultural monument, which I name as Natal cascudiana. In this sense, I investigate the process of Câmara Cascudo s monumentalization by the city of Natal, questioning the way his life has been articulated to the site of his production. Bearing this in mind, I have structured the work in three parts: on the first one, I examine the emerging of this identity relationship considering the intellectual formation of young Cascudinho and the beginnings of his literary activities, verifying the reasons that led him to remain in Natal; on the second part I investigate his appointment as Natal s historian in 1948, discussing the ways through which this intellectual function institutionalized the works of Cascudo and conferred the city with a historical knowledge of itself; and finally, I analyze the constitution of a city memory regarding Cascudo, that has transformed him into spatial marks and urban toponym: names of streets, museum, library, bookstores etc. On these terms, I deal with the biographic gender to achieve a history of the city s spaces, problematizing the monumentalization of Cascudo in Natal, interrogating the emerging of this Natal cascudiana